Effect of Mn in ZnO using DFT calculations: Magnetic and electronic changes - Gallegos, María Victoria (2019)
First principles calculations based on density functional theory (DFT)implemented in the VASP code was applied to study the structural, electronic and magnetic properties of ZnO and Mn-doped ZnO. Lattice parameters, bond lengths, energy band gap and magnetic moment were evaluated after the incorporation of neutral (VO 0 )and charged (VO 2+ )oxygen vacancies on both undoped and Mn-doped ZnO. Neutral oxygen vacancy produces a shrinkage of the distance to its nearest neighbor zinc atoms while the positive oxygen vacancy produces the opposite effect. The Zn?O bond length practically is not affected by incorporation of Mn atom, nevertheless, a magnetic moment is induced (5 μ B )as new states at the band gap zone. The presence of oxygen vacancies strongly decreases magnetic moment for Mn-doped ZnO which could favor a transition from ferromagnetic to antiferromagnetic behaviour. These facts do the system Mn-doped ZnO with vacancies a promising candidate for designing the first antiferromagnetic piezoelectric material.